Scarred hearts. Issue 10 (October 2016) - Gilbey, Peter; Jostrom, Susan
Highlights: This work presents the parallel stories of a physician with a scarred heart and the mother of a child with a scarred heart. The work deals with physician well-being and offers a unique patient carer voice. Both physician, patient and patient carer strive toward the common goal of improved health and extended life. The potential exists for doctor–patient-family solidarity based on mutual respect and shared awareness of human mortality.